Analysing drivers of routine and COVID-19 vaccination in migrants to develop tailored interventions. (20th October 2021) - Crawshaw, AF; Farah, Y; Deal, A; Goldsmith, LP; Carter, J; Rustage, K; Campos-Matos, I; Vandrevala, T; Forster, AS; Hargreaves, S
Abstract: Background: Migrants in Europe are at risk of under-immunisation and may also have lower COVID-19 vaccination intent and uptake. There is an urgent need to better understand the drivers of uptake in these groups to inform the development of migrant-sensitive interventions for COVID-19 vaccination and routine vaccination beyond the pandemic. Methods: We did a systematic review (PROSPERO: CRD42020219214) following PRISMA guidelines to explore factors influencing vaccine uptake in migrants in the EU/EEA and identify determinants of under-immunisation. We also held 3 participatory workshops with multinational migrant community leaders (n = 23) in London, to explore solutions and approaches to strengthen COVID-19 vaccine roll-out. Results: We included 66 papers reporting data on 262, 761 migrants in the review. Numerous access-related factors (e.g. government policy, communication barriers) influenced uptake. Vaccine hesitancy was attributed to lack of information, concerns about side-effects, and cultural beliefs/stigma around specific vaccinations. Migrants who had recently arrived, were older, female or of African and Eastern Mediterranean origin were at risk for under-immunisation for key vaccine-preventable diseases. Migrant community leaders reported considerable hesitancy towards COVID-19 vaccination in their communities and misinformation circulating via social media. Leaders requested support in producing simple COVID-19 guidance that could be translated and adapted locally, alongside more meaningful engagement and partnership-working. Conclusions: Access barriers and vaccine hesitancy may affect vaccine uptake in some migrant populations in Europe, which needs to be urgently addressed for COVID-19 vaccine roll-out but also beyond the pandemic to strengthen uptake of routine vaccinations. Actively involving migrant communities in the planning, co-production and implementation of tailored and targeted approaches will be essential. On behalf of ESGITM. Key messages: Access barriers and vaccine hesitancy (from information gaps, cultural factors) contribute to low vaccine uptake in some migrant populations in the EU/EEA, with implications for COVID-19 vaccination. Meaningful engagement and co-production of tailored approaches with under-immunised migrants are urgently needed to ensure their inclusion in COVID-19 and routine vaccination programmes.